Harm reduction in Cambodia: a disconnect between policy and practice - Chheng Kannarath; Leang Supheap; Thomson Nick; Moore Timothy; Crofts Nick (BMC, 2012)
Abstract In 2003 the Government of Cambodia officially began to recognise that harm reduction was an essential approach to preventing HIV among people who use drugs and their sexual partners. Several programs aiming to control and prevent HIV among drug users have been implemented in Cambodia, mostly in the capital, Phnom Penh. However, there have been ongoing tensions between law enforcement and harm reduction actors, despite several advocacy efforts targeting law enforcement. This study attempts to better understand the implementation of harm reduction in Cambodia and how the policy environment and harm reduction program implementation has intersected with the role of law enforcement officials in Cambodia.